OPTIMALISASI PEMANFAATAN TANAMAN OBAT UNTUK PENINGKATAN KESEHATAN MASYARAKAT PULAU GILI IYANG, SUMENEP - Wahyuni, Tutik Sri; Neny Purwitasari; Farida Ifadotunnikmah; Retno widyowati; Wiwied Ekasari; Abdul Rahem; Dewi Melani Hariyati (Jurusan Farmasi FMIPA Universitas Tadulako, 2024)
Gili Iyang is an island that belong to Madura, that located in Dungkek District, Sumenep Regency, East Java. This island is famous as an oxygen island with the second best oxygen levels in the world. This island also has various natural sources including medicinal. However, some of the existing potentials have not been utilized and processed optimally. Therefore, this activity is focused on optimazing the used of medicinal plants for improving health among communities. This activities were including planting medicinal plants or call â€œTanaman Obatâ€(TOGA). Moreover to improve the understanding about medicinal plan, lecture section about the function of plants and how to prepare the traditional recepi was conducted. Information about medicinal plants for hipertention, diabetic and degenerative diseases such as osteoarthritis and women's health disorders were shared. Workshop about preparation herbal soap from piper betle was also conducted to the community of Gili Iyang . Piper batle was known as antimicrobial that could overcome vaginal discharge disorders. This activity give many advantages to the Gili Iyang Community that could improve the understanding on medicinal plants. The analysis of each participant in answering the question of pretest and posted was calculate. The results showed the right answer improve up to 70%. This result indicate the advantage of this activity to the community of Gili Iyang that consist of Banraas dan Bancamara village. This program is an application of several aspects of the Sustainable Development Goals (SDGs) including health (3), quality education (4), and is a strengthening of national research priorities (PRN) in the fields of Blue-Green Economy and Health.